PROFIL SINDROM METABOLIK DAN ASUPAN MAKAN PADA WANITA PEDESAAN DI POSBINDU PTM DI DESA CILONGOK - Yovita Puri Subardjo; Friska Citra Agustia; Dika Betaditya; Gumintang Ratna Ramadhan (Jurnal Gizi dan Pangan Soedirman, 2022)
MetS (MetS) is a predictor of cardiovascular disease and type 2 Diabetes mellitus. The prevalence of MetS increases not only in the urban area but also in the rural area. Women have a greater risk of MetS than men in some studies. This study was purposed to describe MetS prevalence and pattern of rural area women in the Integrated Development Post of Non-communicable Disease (Posbindu PTM) in Cilongok Rural Area. A population-based cross-sectional study was conducted in Cilongok, Banyumas rural area of Central Java among 63 rural women. Data were collected by interviews; measurement of fasting blood glucose, high-density lipoprotein, and triacylglycerol; measurement of blood pressure and abdominal circumference. Food consumption data were collected by multiply 24-hours food recalls. MetS were categorized by NCEP ATP III 2001 criteria. The prevalence of MetS in rural area women was 31.75%. Age was associated with MetS (p-value 0.038 ;95% CI : 0.983-23.63). Women with MetS have significant differences with women without MetS in the value of fasting blood glucose, high-density lipoprotein, triacylglycerol, blood pressure, and abdominal circumference (p-value <0.05). About 95% of MetS women have a high waist circumference and 80% have a low high-density lipoprotein. MetS women consumed higher energy than women without MetS (p-value <0.05). Conclusion: Prevalence of MetS in Cilongok rural area women was high. High in fasting blood glucose, high-density lipoprotein, triacylglycerol, blood pressure, and abdominal circumference were found to be a predictor of MetS. High energy consumption becomes a risk factor for MetS.